APLIKASI PUPUK ZA DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG DAUN (Allium fistulosum L.) - Saida Saida; Abdul Haris; Sri Wahyuni Rahim (Jurnal Penelitian Pertanian Terapan, 2023)
This research was conducted in Marawi Village, Pinrang Regency, South Sulawesi from March to May 2022. This study aims to determine the best effect of ZA fertilizer dose, cow manure, and the interaction between the two on the growth and production of leek plants with a verticulture system. This research was conducted using a factorial randomized block design (RAK) consisting of 2 factors, the first factor being ZA fertilizer application which consisted of three levels, namely control, dose of 300 kg/ha, and dose of 600 kg/ha. The second factor was the application of cow manure which consisted of three levels, namely the dose of 25 tons/ha, 15 tons/ha, and a dose of 20 tons/ha. There were 9 treatment combinations that were repeated 3 times, so that 27 experimental units were obtained. The results showed that there was an interaction between ZA fertilizer 600 kg/ha and cow manure at a dose of 20 tons/ha had a good effect on the average plant height of 43.90 cm and the longest root length of 26.90 cm. The application of ZA fertilizer 600 kg/ha had a good effect on the average growth of the number of leaves, namely 23.40 strands and the number of tillers per clump, namely 5.37 in leek plants. The application of cow manure 20 tons/ha had a good effect on the average fresh weight of plants per polybag, which was 195.04 g and plant consumption weight per polybag, which was 169.29 g on leks.